Dangerous rotations – Switching from high-dose oxycodone to morphine. (April 2015) - MacKintosh, David; Brady, Angela; Carr, Sally
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction Opioid switching in the management of cancer-related pain is a widely used strategy which relies heavily on the use of published equianalgesic ratios despite acknowledged difficulties which include serious toxicity. Agreement on appropriate conversion ratios has yet to be reached with oral oxycodone to oral morphine (O:M) ratios of both 1:1.5 and 1:2 being proposed. As part of an assessment of the safety of switching from high-dose oral oxycodone to oral morphine using equianalgesic ratios of 1:1.5 and 1:2 (O:M), we report three cases where uncritical adherence to these published ratios may have been problematic for patient safety. Method Retrospective case review. Results Switching from high-dose oral oxycodone to oral morphine was successfully achieved between 6 and 17% of the predicted oral morphine dose. Final conversion ratios (O:M) were between 1:0.125 and 1:0.25 in contrast to published ratios of 1:1.5 and 1:2. Discussion The effective doses of morphine were well below those predicted by agreed standards. Unthinking adherence to published equianalgesic ratios of either 1:1.5 or 1:2 may have placed the patients at risk of serious toxicity. Dose reduction for incomplete cross-tolerance would have modified but not abolished the risk. With high-dose switches, we recommend an initial 'test dose' of immediate release morphine of no greater than 10% of the predicted morphine dose. An alternative is gradual reduction of oxycodone while titrating morphine upwards; this approach, however, while safe, is time consuming and does not address the need for urgent pain relief.